Some aspects of leadership in the neo-Hindu religious movement: The case of the Art of Living Foundation in Lithuania - Ališauskienė, Milda (Acta Orientalia Vilnensia, 2010)
Vilnius UniversityThe leader in any new religious group is a very important person and a key feature in the establishment of the organized religion. The special role and place for the leader is found in the so-called spiritual groups—the Neo-Hindu religious movements. Although such groups do not relate themselves to any religious phenomena in general, an analysis of their activities reveals the traditional importance of their leader in doctrinal and organizational development. The aim of this article is to analyze the role and place of Ravi Shankar, the leader of the Art of Living Foundation (AoLF), the process of his charismatization, as well as the attitudes of members toward the leader and his legitimization from the perspective of the sociology of religion. The work is based on the analysis of certain official documents of the organization and through narratives of members from Lithuania and Denmark. The article focuses on the case of Lithuania, which is revealed through the comparison of the data from Denmark. The analysis revealed that individuals expressed special attitudes toward the leader of the group: that, on the one hand, modern individuals sought liberation from institutionalized religion but at the same time they were searching for spiritual authority. Interviews with members of the AoLF revealed diverse concepts of the spiritual leader. Contrary to the traditionally accepted understanding of a spiritual leader as the head of authority, the narratives revealed an understanding of the spiritual leader as both an advisor and a service provider.